Penerapan Problem Based Learning Berbantuan Media Monopoli Cerdas untuk Meningkatkan Minat dan Hasil Belajar Kognitif Siswa di MAS Al-Muslihun - Fatimah, Nurul; Imam Bukhori Muslim; Sudiarti, Diah (RUKASI: Jurnal Ilmiah Perkembangan Pendidikan dan Pembelajaran, 2024)
The study was conducted with the aim of increasing the interest and cognitive learning outcomes of grade XI students of MAS Al-Muslihun. The Problem Based Learning model and smart monopoly media are expected to spur students' enthusiasm and enthusiasm in participating in learning activities so that students' interest and learning outcomes increase. The type of research used is classroom action research consisting of 2 cycles, each cycle consists of 4 stages, namely planning, implementation, observation, and reflection. The subjects of this study were all grade XI students, the sample of this study amounted to 18 students. This research data was obtained through tests, observations, interviews and documentation. The results showed an increase in student interest in learning starting from the pre-cycle by 6.3%, while in cycle I to cycle II it increased by 28.15%. As for students' cognitive learning outcomes, it increased from pre-cycle to cycle I by 16.7%, while from cycle I to cycle II it increased by 38.89%. Based on the results obtained, it can be concluded that the application of problem-based learning assisted by smart monopoly media can increase students' interest and cognitive learning outcomes at MAS Al-Muslihun.